Metacognitions on pain, functionality and intensity of pain in women with fibromyalgia (2020)
ABSTRACT: To determine the explanatory capacity of pain metacognitions and beliefsover the functionality, coping and pain intensity, following the Model ofSelf-Regulatory Executive Functions (S-REF) in a sample of women withfibromyalgia from Medellín and its Metropolitan Area. Method: Metacog-nitions Scale on Symptom Control, Pain Self-efficacy Questionnaire,Chronic Pain Catastrophizing Scale, Chronic Pain Coping Questionnaire,WHODAS 2.0 Scale, and Pain Intensity Numerical Scale. The sample wasrepresented by 108 women between 24 and 60 years old with a diagnosisof fibromyalgia. A modeling process was carried out through an analysisof structural equations. Results: The final model fails to fit. Despite this,the analysis suggests that negative metacognitions and pain self-efficacyhave an effect over the tendency to catastrophizing. The latter and thepain self-efficacy are the main mediators in the effects of functionality.The intensity of pain is not determined by the metacognitions related to it.